Poskus širjenja protestantizma med gradiščanskimi Hrvati: pesmarici iz leta 1609 in 1611 - Neweklowsky, Gerhard (Slavia Centralis, 2020)
An attempt to install Protestantism among Western Hungarian (Burgenland) CroatsThe article describes the motives for publishing the two oldest Croatian Protestant hymn books printed in Burgenland, then Hungary, today Austria, the Duševne pesne of 1609 and 1611. They contain translations of German, Latin, Hungarian, and, possibly, Slovenian Protestant hymns. Their author, Grgur Mekinić, was invited to serve as a Protestant pastor in Deutschkreuz in order to disseminate Protestantism among the Croats. However, he did not succeed; the Croats remained Catholic. The language of the hymns is the Ikavian–ekavian Čakavian dialect of Croatian, which is still spoken in Burgenland today. However, there are other linguistic elements, too. The hymn books cannot be considered as the beginning of Burgenland Croatian literature, because they were forbidden and consequently entirely forgotten.
Keywords: Protestantism in Burgenland; Protestant hymns; relations to Slovene Protestantism; Burgenland Croatian language; Čakavian dialect; South Slavic dialectology